Nación y cultura política. El caso de una localidad colombiana en el período de la violencia (2007)
ABSTRACT: Research-based local political culture in the period of Violence, are some elements of a case study on local political culture in the municipality of La Estrella Antioquia between the years 1946 to 1953. Show is set as the Colombian nation, implies the recognition that its political culture built from the region and the local was characterized by the middle of the twentieth century by the bipartisan confrontation and the relationship with the Catholic religion, triggering the phenomenon known as the Violence.